Coverage of the 2019 Eastern equine encephalitis virus outbreak on news media - Basch, Corey H. (Health Promot Perspect, 2020)
Background: The media plays as an important role in delivering information about emergent issues, such as the Eastern equine encephalitis virus (EEEV) outbreak of 2019. As such, there has been an increase in news coverage of vector-borne disease coverage due to a rise in emerging or re-emerging arboviruses. Methods: The purpose of this study was to describe the content of news clips related to the recent (2019) EEEV outbreak in the United States. Results: Only 3 of the important topics identified were mentioned in a majority of the 110videos analyzed. These topics were, mosquito mentioned as transmitter, prevention by repellent/pesticide, and geography. Thus, many aspects of EEEV were lacking in coverage. Conclusion: A priority for public health professionals should be to engage in discourse with newsmedia to assure that information disseminated via news channels is not vague or misleading.